2021
DOI: 10.55705/cmbr.2021.138880.1003
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of genetic polymorphisms of the human cytochrome P450 3A4 in rivaroxaban-treated patients

Abstract: Rivaroxaban is an anticoagulant drug that prevents forming of blood clots. In addition, it can be administered to prevent and treat thrombotic diseases such as atrial fibrillation, cardiac arrhythmia, heart valve disease, orthopedic surgery, and thrombophilia to reduce the risk of thrombosis. Various factors such as age, gender, diet, medications, and genetic factors effectively determine the dose of rivaroxaban. Genetic variability in drug-metabolizing enzymes, including the cytochrome P450 (CYP450) enzymes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…It indicated that Dex can reduce the incidence of cognitive dysfunction under CPB cardiac surgery. Dex can improve immunity and reduce inflammation (18)(19)(20). After cardiac surgery under CPB, the complement system was activated, which stimulated the release of inflammatory factors, and caused inflammation.…”
Section: Results Of Fluorescence Quantitative Pcrmentioning
confidence: 99%
“…It indicated that Dex can reduce the incidence of cognitive dysfunction under CPB cardiac surgery. Dex can improve immunity and reduce inflammation (18)(19)(20). After cardiac surgery under CPB, the complement system was activated, which stimulated the release of inflammatory factors, and caused inflammation.…”
Section: Results Of Fluorescence Quantitative Pcrmentioning
confidence: 99%
“…Microbial infections, heart diseases, and cancers are the main health-threatening diseases worldwide [1][2][3]. Antibiotic resistance is a threat in many hospitals, and mortality and death due to infections in patients are increasing dramatically [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a few SNPs were described for the CYP3A4 and CYP3A5 genes. The CYP3A5*3 and CYP3A5*6 alleles were found to be the underlying cause for alternative splicing and protein truncation, resulting in the absence of functional CYP3A5 from liver tissue 33 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%